(untitled) (Journal of the College of Basic Education, 2026)
The current research aimed to determine the effect of the Philosophers’ Chairs strategy on the achievement and development of caring thinking among second-year intermediate school students in social studies during the 2024-2025 academic year. The study sample consisted of two groups: an experimental group of 37 students and a control group of 38 students. The researcher used an achievement test consisting of 40 items and a caring thinking scale consisting of 50 items. The results showed a statistically significant difference in favor of the students in the experimental group who studied using the Philosophers’ Chairs strategy, in addition to the development of their caring thinking. The researcher concluded the following: The results of applying the Philosophers’ Chairs strategy demonstrated its effectiveness in reorganizing the cognitive structure of learning, as it provided the research sample (the experimental group) with the opportunity to actively construct their knowledge through dialogue, discussion, and in-depth cognitive processing. This positively impacted the improvement of their academic performance and the development of caring thinking among the students in the experimental group. The Philosophers’ Chairs strategy enabled the students in the experimental group to connect theory with practice, facilitating their understanding of social studies knowledge and contributing to improved academic performance and the development of caring thinking.